Characterization of Antileishmanial Compounds from Lawsonia inermis L. Leaves Using Semi-High Resolution Antileishmanial Profiling Combined with HPLC-HRMS-SPE-NMR - Iqbal, Kashif; Iqbal, Javeid; Staerk, Dan; Kongstad, Kenneth T. (Frontiers in Pharmacology, 2017)
This work describes an analytical platform based on semi-high-resolution antileishmanial profiling combined with hyphenation of high-performance liquid chromatography - high-resolution mass spectrometry – solid-phase extraction - nuclear magnetic resonance spectroscopy, i.e., semiHR-antileishmanial assay/HPLC-HRMS-SPE-NMR. The platform enables fast pinpointing of HPLC peaks representing Leishmania tropica inhibitors in complex matrices, with subsequent structural identification of targeted inhibitors. Active analytes were cumulatively trapped on SPE cartridges and the structures elucidated by analysis of NMR spectra obtained in the HPLC-HRMS-SPE-NMR mode. This led to the identification of six known compounds 2,4,6-trihydroxyacetophenone-2-O-B-D-glucopyranoside (1), lalioside (2), luteolin-4′-O-B-D-glucopyranoside (3), apigenin-4′-O-B-D-glucopyranoside (4), luteolin (5), and apigenin (6). IC50 of the active compounds were determined with luteolin being the most potent inhibitor with an IC50 value of 4.15 ug/ml. The platform proved to be an efficient method for the identification of L. tropica inhibitors.